Exploring Digital Literacy Practices in Indonesia: A Contestation Analysis of the Discourse on Prophet Muhammad's Descent on Youtube Channel - Yaqin, Haqqul (Proceedings of International Conference on Muslim Society and Thought, 2024)
The publication of KH. Imaduddin Utsman al Bantani's book on the disconnection of the Indonesian Arab lineage from the Prophet Muhammad (May 2023) has elicited a diverse range of reactions, even in the neighboring country of Malaysia. The merits and demerits of responding to the contents of the book are currently being debated on news platforms in Indonesia, including both traditional and digital media, as well as on social media platforms such as Tiktok, IG, and YouTube. This article examines the public's views on the pros and cons of YouTube. The YouTube content to be analyzed was released on several channels between July 2023 and June 2024. As one of the world's most significant social media platforms, YouTube boasts 137 million users in Indonesia as of October 2023, making it an ideal platform for disseminating certain understandings and views in Indonesia. This study aimed to address two key questions. First, how is the discourse on the Prophet's descendants constructed on YouTube channels? Second, how is the response and counter-discourse on the Prophet's descent carried out? To address these two research problems, a qualitative research approach was employed, specifically critical discourse analysis. This research focuses on efforts to understand and study discourse as an element that forms power and ideology in society, particularly with regard to the issue of fighting over the Prophet's descendants, which forms a unique relationship within a discourse.